(untitled) (Economics and region, 2024)
The article comprehensively examines the impact of tax policy on the development of the tourism industry in Ukraine. It explores the relationship between tax revenues generated from various types of economic activities within the tourism sector and their contributions to the formation of state and local budgets. Emphasis is placed on analyzing taxes paid by key players in the industry, including hotels, tour operators, travel agencies, alternative accommodation facilities, campsites, and other stakeholders. Key aspects of taxation for each activity type are presented, covering the payment of general taxes such as corporate profit tax, value-added tax, and personal income tax. The analysis also includes other fiscal obligations like environmental tax, land tax, rent payments, and local taxes and fees, such as tourist tax, transport tax, real estate tax, and the unified tax for entrepreneurs under simplified taxation systems. Taxation specifics are outlined based on the legal status of entities (legal entities or individuals), the choice of taxation system (general or simplified), and the extent of resource utilization and land ownership. The article delves into critical challenges of tax regulation affecting the tourism sector. It is determined that hotels, travel agencies, and alternative accommodation providers face the greatest fiscal pressures due to tourist taxes and environmental taxes. In response to these challenges, the paper proposes measures to improve tax policy, including reducing the tax burden on small businesses, streamlining tax payment procedures, and implementing preferential taxation mechanisms to foster industry growth. Special attention is given to the tourism industry’s broader impact on regional development and its role in fostering a sustainable national economy. The importance of targeted fiscal incentives to enhance tourism infrastructure is emphasized, highlighting their potential to attract domestic and foreign investment, boost employment, and integrate Ukraine into the global tourism landscape. By addressing existing fiscal inefficiencies and implementing proactive measures, the tourism industry can serve as a cornerstone for economic resilience and growth in Ukraine, particularly in the face of contemporary global challenges. Moreover, the article encourages the adoption of a balanced fiscal framework that aligns tax obligations with the financial capacities of tourism businesses while ensuring that revenues are reinvested into the sector’s development. This approach is vital for building a competitive and inclusive tourism ecosystem that supports innovation, enhances regional attractiveness, and promotes cultural exchange.